Experimental study of pH effect on uranium (UVI) particle formation and transport through quartz sand in alkaline 0.1 M sodium chloride solutions - Kirby, Matthew Edward; Watson, Jonathan Stuart; Najorka, Jens; Kenney, Janice; Krevor, Samuel; Weiss, Dominik J. (My University, 2020)
A thorough understanding of the aqueous uranium VI (UVI) chemistry in alkaline, sodium containing solutions is imperative to address a wide range of critical challenges in environmental engineering, including nuclear waste management. The aim of the present study was to characterise experimentally in more detail the control of pH on the removal of UVI from aqueous alkaline solutions through particle formation and on subsequent transport through porous media. We conducted first static batch experiments in the pH range between 10.5 and 12.5 containing 10 ppm UVI in 0.1 M NaCl solutions and examined the particles formed using filtration, dynamic light scattering, transition electron microscopy and X-ray powder diffraction. We found that at pH 10.5 and 11.5, between 75 and 96 % of UVI was removed from the solutions as clarkeite and studtite over a period of 48 h, forming particles with hydrodynamic diameters of 640 ± 111 nm and 837 ± 142 nm, respectively and representing aggregates of 10′s nm sized crystals randomly orientated. At pH 12.5, the formation of particles >0.2 μm became insignificant and no UVI was removed from solution. The mobility of UVI in these solutions was further studied using column experiments through quartz sand. We found that at pH 10.5 and 11.5, UVI containing particles were immobilised near the column inlet, likely due physical immobilisation of the particles (particle straining). At pH 12.5, however, UVI quantitatively eluted from the columns in the filter fraction <0.2 μm. The findings of our study reinforce a strong control of solution pH on particle size and U removal in alkaline solutions and subsequently on mobility of U through quartz porous media.
Keywords: pH; particle; formation; alkaline; NaCl; uranium